#TITLE_ALTERNATIVE# - NURMINDHA , RISKA
This final project report summarizes the design, realization, and measurement of microstrip antenna with or without parasitic element which operates at frequency of 2.5 GHz for the receiver and 2.65 GHz for the transmitter. This antenna is aimed to be used by mobile satellite application with possibility to be used by other application. The antenna is designed using Ansoft Corporation's Ensemble version 7. The dimension of microstrip antenna is designed using available equations, which is later iterated to achieve optimized value. The realized antenna with parasitic elements improves antenna's gain and bandwidth. The antenna will have approximately 7.3 dB of gain and bandwidth greater than 300 MHz for both transmitter and receiver. The reactive impedance for the antenna is less than one ohm, much smaller than twenty ohm, which is the reactive impedance of the antenna without parasitic element.